The H2S Donor Sodium Thiosulfate (Na2S2O3) Does Not Improve Inflammation and Organ Damage After Hemorrhagic Shock in Cardiovascular Healthy Swine - Messerer, David Alexander Christian; Gaessler, Holger; Hoffmann, Andrea; Gröger, Michael; Benz, Kathrin; Huhn, Aileen; Hezel, Felix; Calzia, Enrico; Radermacher, Peter; Datzmann, Thomas (Frontiers in Immunology, 2022)
We previously demonstrated marked lung-protective properties of the H2S donor sodium thiosulfate (Na2S2O3, STS) in a blinded, randomized, controlled, long-term, resuscitated porcine model of "human-sized" swine with coronary artery disease, i.e., with decreased expression of the H2S-producing enzyme cystathionine-γ-lyase (CSE). We confirmed these beneficial effects of STS by attenuation of lung, liver and kidney injury in mice with genetic CSE deletion (CSE-ko) undergoing trauma-and-hemorrhage and subsequent intensive care-based resuscitation. However, we had previously also shown that any possible efficacy of a therapeutic intervention in shock states depends both on the severity of shock as well as on the presence or absence of chronic underlying co-morbidity. Therefore, this prospective, randomized, controlled, blinded experimental study investigated the effects of the STS in cardiovascular healthy swine. After anesthesia and surgical instrumentation, 17 adult Bretoncelles-Meishan-Willebrand pigs were subjected to 3 hours of hemorrhage by removal of 30% of the blood volume and titration of the mean arterial pressure (MAP) ≈ 40 ± 5 mmHg. Afterwards, the animals received standardized resuscitation including re-transfusion of shed blood, fluids, and, if needed, continuous i.v. noradrenaline to maintain MAP at pre-shock values. Animals were randomly allocated to either receive Na2S2O3 or vehicle control starting 2 hours after initiation of shock until 24 hours of resuscitation. The administration of Na2S2O3 did not alter survival during the observation period of 68 h after the initiation of shock. No differences in cardio-circulatory functions were noted despite a significantly higher cardiac output, which coincided with significantly more pronounced lactic acidosis at 24 hours of resuscitation in the Na2S2O3 group. Parameters of liver, lung, and kidney function and injury were similar in both groups. However, urine output was significantly higher in the Na2S2O3 group at 24 hours of treatment. Taken together, this study reports no beneficial effect of Na2S2O3 in a clinically relevant model of hemorrhagic shock-and-resuscitation in animals without underlying chronic cardiovascular co-morbidity.